2014
DOI: 10.1002/cmdc.201402240
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antiamoebic Activity Evaluation and Docking Studies of Metronidazole–Triazole Hybrids

Abstract: An in-house database of 520 compounds was docked against Entamoeba histolytica thioredoxin reductase (EhTrR), a promising target for the treatment of amoebiasis. Amongst these, some metronidazole (MTZ)-triazole hybrids were ranked high, with docking scores from -10.23 to -7.56. Studies of the binding orientations and conformations show that the head groups of MTZ-triazole hybrids interact with the arginine residues within the binding pocket of EhTrR, making it clear that such is the optimal and most reliable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 38 publications
0
19
1
Order By: Relevance
“…e-Pharmacophore methodology 24 combines the advantages of both structure-based and ligand-based drug-design theories, and can be employed rapidly to screen the ligands based on pharmacophore properties. 25 Using the e-pharmacophore protocol from the scripts, pharmacophore sites were generated from protein with redocked crystal–ligand complexes, preserving a maximum of seven pharmacophore features as default. Pharmacophore chemical properties are hydrogen-bond acceptor (A), represented as vectors, hydrogen-bond donor (D) as projected points, aromatic ring (R) as ring, positive ionizable (P), and negative ionizable (N).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…e-Pharmacophore methodology 24 combines the advantages of both structure-based and ligand-based drug-design theories, and can be employed rapidly to screen the ligands based on pharmacophore properties. 25 Using the e-pharmacophore protocol from the scripts, pharmacophore sites were generated from protein with redocked crystal–ligand complexes, preserving a maximum of seven pharmacophore features as default. Pharmacophore chemical properties are hydrogen-bond acceptor (A), represented as vectors, hydrogen-bond donor (D) as projected points, aromatic ring (R) as ring, positive ionizable (P), and negative ionizable (N).…”
Section: Methodsmentioning
confidence: 99%
“…QikProp version 3.6 (Schrödinger suite) was used to calculate the ADME (absorption, distribution, metabolism, and excretion) properties of the ligands. 25 , 26 This module was used to analyze the relevant pharmaceutical properties, including human oral absorption, central nervous system activity, predicted brain/blood partition coefficient (QPlogBB), octanol/water and water/gas log Ps, log S, Caco-2, MDCK cell permeability, Lipinski rule of five, and Jorgensen rule of three. The compounds obtained from e-pharmacophore screening were selected as input molecules for analyzing the ADME properties.…”
Section: Methodsmentioning
confidence: 99%
“…Entamoeba histolytica MTT-Assay Thioredoxin reductase In order to explore the possible antiamoebic potential of newly synthesized metronidazole-hydrazone conjugates (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13), all the compounds were screened against HM1: IMSS strain of E. histolytica by microdilution method 15 and the results were compared with the most widely used antiamoebic drug MNZ that had 50% inhibitory concentration (IC 50 ) 1.81 μM in our experiments. All the title compounds (2-13) exhibited better IC 50 values (0.20-7.12 μM) than the compound 1 (IC 50 = 11.48 μM).…”
Section: Abstract: Metronidazole Amoebiasismentioning
confidence: 99%
“…In this paper, we herein report the synthesis, antiamoebic activity, molecular docking and lipophilic studies of metronidazole hydrazone conjugates ( Figure 4). Metronidazole hydrazone conjugates (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13) were synthesized and screened in vitro for antiamoebic activity against HM1: IMSS strain of Entamoeba histolytica. Six compounds were found to be better inhibitors of E. histolytica than the reference drug metronidazole.…”
mentioning
confidence: 99%
“…In this context, MTZ‐triazole conjugates have recently reported by several research teams. Negi and coworkers have shown that the hydroxyl group of MTZ is amenable to modification . They have replaced the hydroxyl with 1,2,3‐triazolyl moiety utilizing a modular synthesis through the copper(I)‐catalyzed azide‐alkyne cycloaddition (CuAAC).…”
Section: Introductionmentioning
confidence: 99%